Enhancing Robustness of Sortase A by Loop Engineering and Backbone Cyclization. Issue 60 (16th September 2020) - Zou, Zhi; Mate, Diana M.; Nöth, Maximilian; Jakob, Felix; Schwaneberg, Ulrich
Abstract: Invited for the cover of this issue is Ulrich Schwaneberg and co‐workers at RWTH Aachen University and DWI Leibniz‐Institut für Interaktive Materialien. The image depicts a loop engineered, and backbone cyclized Staphylococcus aureus sortase A which shows enhanced robustness in site‐specific protein and peptide modifications. Read the full text of the article at 10.1002/chem.202002740 . Abstract : " Sortase‐mediated ligation, also known as sortagging, has emerged as one of the most popular and powerful methodologies for site‐specific protein modifications. The robustness of the engineered Staphylococcus aureus sortase A variant CyM6 against denaturating agents and elevated temperatures increased by loop engineering and subsequent backbone cyclization ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 13568 ff. (DOI: 10.1002/chem.202002740 ).